Effects of Tillage and Different Thicknesses of Water Hyacinth Mulch on - Kabir, MA; Rahim, MA; Taj, HF El; Majumder, DAN; Mahmood, Shreef (Journal of Environmental Science and Natural Resources, 2012)
Different growth parameters of garlic as well as bulb yield were found significant in respect of the treatments. Nonetheless, the combination of 10 cm thick mulch with zero tillage produced the highest yield (9.92 t/ha). On the contrary, the lowest yield (4.23 t/ha) was obtained from no mulch with zero tillage. Economic analysis among the treatment combinations showed that the total cost of production was the highest in 12 cm thick mulch with conventional tillage, however, the highest BCR (2.89) was recorded from the zero tillage with 10cm mulch. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10126 J. Environ. Sci. & Natural Resources, 4(2): 19-26, 2011